Case report: Resection of a giant right ventricular myxoma - Rao, Jin; Yang, Qian; Yin, Liang; Yu, Yue; Xi, Wang; Xu, Jibin; Zhang, Yufeng; Wang, Zhinong (Frontiers in Surgery, 2023)
Myxoma comprises the main subtype of all benign cardiac tumors, tending to be more common in women and occur mostly in the left and right atrium. The classic clinical presentations of it include intracardiac obstruction, embolization, systemic or constitutional fever, and so on in a decreasing order. Serval imaging techniques such as echocardiography, computed tomography, and angiocardiography contribute to myxoma diagnosis, ruling out significant coronary diseases, and assessments of myocardial invasion and tumor involvement of adjacent structures. Surgical resection is the only effective therapeutic option for patients with cardiac myxoma. Here, we reported a unique case of a middle-aged man who presented with a giant myxoma and a 3-day history of chest tightness and shortness of breath after activities. Subsequently, transthoracic echocardiography revealed a mass of solid echodensity located within the right ventricle complicated with abnormal hemodynamics. The cardiac computed tomographic angiography showed a large homogeneous density filling defect consuming the most part of right ventricle and protruding from beat to beat. Surgical resection and histological study later successfully confirmed the diagnosis, and patient’s postoperative recovery course was uneventful.